(untitled) (Jurnal Destinasi Pariwisata, 2026)
This study examines the effect of virtual experience on visit intention toward Mount Bromo, with fear of missing out (FOMO) as a mediating variable, using the Mount Bromo map on Roblox as the research context. The research applies a quantitative explanatory approach using a questionnaire survey with a Likert scale. Data analysis includes instrument testing, regression analysis, and mediation testing using a bootstrapping approach. The findings indicate that virtual experience positively influences visit intention, and FOMO has a significant effect on visit intention. Moreover, FOMO is found to partially mediate the relationship between virtual experience and visit intention. These results suggest that immersive virtual experience can strengthen intentions to visit real-world tourism destinations, particularly when such experience trigger psychological pressure to keep up with popular trends and experience.